Activation of oxytocin neurons in the paraventricular nucleus drives cardiac sympathetic nerve activation following myocardial infarction in rats. (December 2018) - Roy, Ranjan; Augustine, Rachael; Brown, Colin; Schwenke, Daryl
Abstract Myocardial infarction (MI) initiates an increase in cardiac sympathetic nerve activity (SNA) that facilitates potentially fatal arrhythmias. The mechanism(s) underpinning sympathetic activation remain unclear. Some neuronal populations within the hypothalamic paraventricular nucleus (PVN) have been implicated in SNA. This study elucidated the role of the PVN in triggering cardiac SNA following MI (left anterior descending coronary artery ligation). By means of c-Fos, oxytocin, and vasopressin immunohistochemistry accompanied by retrograde tracing we showed that MI activates parvocellular oxytocin neurons projecting to the rostral ventral lateral medulla. Central inhibition of oxytocin receptors using atosiban (4.5 µg in 5 µl, i.c.v.), or retosiban (3 mg/kg, i.v.), prevented the MI-induced increase in SNA and reduced the incidence of ventricular arrhythmias and mortality. In conclusion, pre-autonomic oxytocin neurons can drive the increase in cardiac SNA following MI and peripheral administration of an oxytocin receptor blocker could be a plausible therapeutic strategy to improve outcomes for MI patients. Roy et al. showed that activation of parvocellular pre-autonomic oxytocin neurons increased sympathetic nerve activity following myocardial infarction. This and other aberrant physiological changes induced by acute myocardial infarction were decreased by oxytocin receptor antagonists, hinting to their potential therapeutic role.